A method for preparing a high-temperature molten salt corrosion-resistant boronized layer on a stainless steel surface and a stainless steel product

CN122979815APending Publication Date: 2026-10-27BEIJING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610991887.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

316L不锈钢作为低温熔盐发电系统中管道、阀门及储罐等部件的常用基材,其对高温氯化物熔盐的耐腐蚀能力有限,无法满足实际应用需求

Benefits of technology

本发明提出一种不锈钢表面耐高温熔盐腐蚀渗硼层的制备方法及不锈钢制品,本发明的制备方法工艺步骤简洁,仅需对不锈钢基体进行常规的表面预处理后直接进行包埋渗硼处理,无需复杂的凝胶配置、磁控溅射、真空退火或堆焊热输入控制等苛刻步骤,工艺流程大幅简化,操作难度低,对设备要求低,具有良好的工艺经济性和可推广性;本发明的方法在不锈钢表面形成的渗硼层致密均匀且与基体结合良好,经700℃的MgCl2-KCl-NaCl(55wt%-20.5wt%-24.5wt%)熔盐腐蚀400h后,渗硼样品的腐蚀深度仅为28.6μm,远低于未处理基体的134μm,腐蚀深度降低至基体样品的约五分之一,耐蚀性能提升极为显著,同时本发明的方法对高温氯化物熔盐蒸汽腐蚀同样具有优良的防护效果,渗硼层在蒸汽腐蚀后无腐蚀孔隙且保持致密,有效抑制了基体的脱铬贫化现象,解决了现有技术中不锈钢在高温氯化物熔盐及蒸汽环境下耐腐蚀能力不足的问题;此外,本发明方法中所用渗硼剂原料来源广泛、成本低廉,对工件形状要求小,渗硼后渗剂残留易于去除,具有显著的经济性和实用性,可广泛应用于聚光太阳能发电系统、高温熔盐储能系统等领域的管道、阀门及储罐等不锈钢部件的表面防护。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979815A_ABST
    Figure CN122979815A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a high-temperature molten salt corrosion-resistant boronized layer on a stainless steel surface and a stainless steel product, and belongs to the technical field of metal material surface protection. The method comprises the following steps: performing surface pretreatment on a stainless steel base body; embedding the base body into a boronizing agent, heating to a boronizing temperature under a protective atmosphere, and then performing heat preservation and subsequent cooling; and removing residual boronizing agent on the surface. The boronized layer prepared by the method is dense and uniform. After being subjected to 400h of MgCl2-KCl-NaCl molten salt corrosion at 700 DEG C, the corrosion depth is only 28.6 mu m, which is far lower than 134 mu m of the untreated base body. In addition, the boronized layer has no corrosion pores in a molten salt vapor environment, and the base body has no chromium-depleted phenomenon. The method is simple in process and low in cost, and can be applied to the surface protection of stainless steel parts such as pipelines, valves and storage tanks in a high-temperature molten salt environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal material surface protection technology, specifically to a method for preparing a high-temperature molten salt corrosion resistant boronizing layer on a stainless steel surface and stainless steel products thereof. Background Technology

[0002] Concentrated solar power (CSP) systems are a new type of renewable energy system that utilizes high- and low-temperature molten salt for heat transfer, converting thermal energy into electrical energy. Next-generation molten salt power generation designs employ NaCl-KCl-MgCl2 molten salt, achieving higher operating temperatures and power generation efficiency, but also placing more stringent demands on the corrosion resistance of metallic materials. 316L stainless steel, a commonly used base material for pipes, valves, and storage tanks in low-temperature molten salt power generation systems, has limited resistance to high-temperature chloride molten salt corrosion, failing to meet practical application requirements. To address this issue, preparing corrosion-resistant coatings on the stainless steel surface is currently the mainstream technological approach.

[0003] In the prior art, various methods for preparing protective coatings on stainless steel surfaces have been disclosed. For example, patent CN118792611A discloses a method for preparing a chloride-resistant molten salt corrosion-resistant layer by embedding aluminizing and thermal diffusion. This method uses 310S, 347H stainless steel, and Inconel 625 nickel-based alloy as substrates. After sanding and polishing, aluminizing is performed using a powder embedding aluminizing agent composed of Al powder, a NH4Cl and AlCl3 compound catalyst, and Al2O3 powder. Subsequently, thermal diffusion treatment is carried out in an air atmosphere, ultimately forming an Al2O3 protective layer on the substrate surface. Patent CN117587389A discloses a method for preparing an alumina-based anti-corrosion coating on the surface of 310S stainless steel. First, an aluminum sol is prepared by acidification sol-gel method. The stainless steel is then immersed in the aluminum sol in a chemical bath, followed by high-temperature heat treatment to obtain the alumina coating. Patent CN118879103A uses (AlTiZrNiCr)O... x Multi-principal element metal oxide (high-entropy oxide) coating systems are applied to molten salt corrosion protection of stainless steel. The target material is prepared by spark plasma sintering, and then the coating is deposited on the surface of 310L stainless steel by reactive magnetron sputtering. Patent CN113369652A discloses a method of depositing Tribaloy T400 alloy powder onto the surface of 316H stainless steel using plasma powder cladding or tungsten inert gas welding to improve the wear resistance and high-temperature molten salt corrosion resistance of the substrate surface. Patent CN117467957A discloses a protective method based on magnetron sputtering of pure molybdenum coating combined with vacuum annealing. After depositing a molybdenum coating on the surface of 304 stainless steel, it undergoes vacuum annealing at 800℃, forming a Mo-Fe-Cr interdiffusion layer between the coating and the substrate to enhance the coating's adhesion and corrosion resistance.

[0004] However, all of the aforementioned existing technical solutions have varying degrees of drawbacks. The aluminizing or aluminosol processes described in patents CN118792611A and CN117587389A are quite complex, involving multiple steps such as pretreatment, aluminizing / impregnation, and thermal diffusion / heat treatment. Furthermore, the aluminizing process requires strict control of the aluminizing agent composition and sealing conditions, resulting in a narrow process window. Patent CN118879103A involves multiple steps including high-entropy oxide target preparation, spark plasma sintering, and reactive magnetron sputtering, leading to high equipment investment and manufacturing costs. The welding method described in patent CN113369652A requires extremely stringent window control (840–1080 J / mm) of welding heat input to balance hardness and corrosion resistance while avoiding microcracks; this process is difficult to control and demands extremely high skill levels from operators. The molybdenum coating method described in patent CN117467957A requires first depositing a molybdenum coating by magnetron sputtering, followed by vacuum annealing. This process is time-consuming and requires specialized vacuum packaging equipment, resulting in high complexity. Furthermore, existing methods for preparing boron-impregnated layers or coatings often require prolonged processing at high temperatures, and residual impregnating agents are difficult to remove in some processes, increasing the cost and difficulty of subsequent treatments. Therefore, there is an urgent need for a simple, low-cost method for preparing boron-impregnated layers that can effectively improve the corrosion resistance of stainless steel in high-temperature chloride molten salt (especially unpurified molten salt) and its vapor environment. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a high-temperature molten salt corrosion resistant boronizing layer on a stainless steel surface and stainless steel products.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This application provides a method for preparing a high-temperature molten salt corrosion resistant boronized layer on a stainless steel surface, comprising the following steps: The stainless steel substrate is pretreated to remove the oxide layer on its surface; The pre-treated stainless steel substrate is embedded in a boronizing agent, heated to the boronizing temperature under a protective atmosphere and held at that temperature, and then cooled to room temperature. The cooled stainless steel substrate is removed from the boronizing agent, and any residual boronizing agent on its surface is removed.

[0007] Optionally, the stainless steel substrate is 316L stainless steel.

[0008] Optionally, the protective atmosphere is argon, and the atmosphere surrounding the stainless steel substrate and the boronizing agent is evacuated before heating.

[0009] Optionally, the boronizing agent is mixed and dried before use.

[0010] A stainless steel article having a boronized layer prepared by the above method on its surface.

[0011] Optionally, the thickness of the boronized layer is 30 μm.

[0012] Optionally, after the stainless steel product is corroded in MgCl2-KCl-NaCl molten salt at a temperature T2 of 700℃ for a time t2 of 400h, the corrosion depth D of the boronized layer satisfies D≤28.6μm; The mass percentages of each component in the MgCl2-KCl-NaCl molten salt are as follows: MgCl2 55wt%, KCl2 0.5wt%, and NaCl2 4.5wt%. The wt% represents the percentage of the mass of each component in the total mass of the molten salt. D represents the corrosion depth in μm. T2 represents the corrosion temperature in °C. t2 represents the corrosion time in h.

[0013] Optionally, the MgCl2-KCl-NaCl molten salt is an unpurified molten salt.

[0014] Optionally, after the stainless steel product is corroded in the steam environment of the molten salt, the boronized layer on its surface is free of corrosion pores and remains dense, and the substrate of the stainless steel product does not exhibit a depletion phenomenon in the region adjacent to the boronized layer where the mass percentage of chromium is lower than the intrinsic content of the substrate due to corrosion.

[0015] Optionally, the stainless steel product is a pipe, valve, or storage tank used in a high-temperature molten salt environment.

[0016] Compared with the prior art, this application has the following beneficial effects: This invention proposes a method for preparing a high-temperature molten salt corrosion-resistant boron-impregnated layer on stainless steel surfaces and stainless steel products thereof. The preparation method of this invention features simple process steps, requiring only conventional surface pretreatment of the stainless steel substrate followed by direct embedding and boronizing treatment. It eliminates the need for complex gel preparation, magnetron sputtering, vacuum annealing, or demanding steps such as welding heat input control. The process is significantly simplified, with low operational difficulty and low equipment requirements, exhibiting good economic efficiency and scalability. The boron-impregnated layer formed on the stainless steel surface by this method is dense, uniform, and well-bonded to the substrate. After 400 hours of molten salt corrosion at 700℃ (MgCl2-KCl-NaCl 55wt%-20.5wt%-24.5wt%), the corrosion depth of the boron-impregnated sample is only 28.6 μm, significantly lower than the required level. The corrosion depth is reduced to about one-fifth of that of the untreated substrate (below 134 μm), resulting in a significant improvement in corrosion resistance. Furthermore, the method of this invention also provides excellent protection against high-temperature chloride molten salt steam corrosion. The boronized layer remains dense and free of corrosion pores after steam corrosion, effectively inhibiting chromium depletion of the substrate and solving the problem of insufficient corrosion resistance of stainless steel in high-temperature chloride molten salt and steam environments in existing technologies. In addition, the boronizing agent used in this invention is widely available and inexpensive, has minimal requirements on workpiece shape, and the residual boronizing agent is easily removed after boronizing, demonstrating significant economic efficiency and practicality. It can be widely applied to the surface protection of stainless steel components such as pipes, valves, and tanks in fields such as concentrated solar power generation systems and high-temperature molten salt energy storage systems. Attached Figure Description

[0017] Figure 1 Flowchart of a method for preparing a high-temperature molten salt corrosion resistant boronizing layer on a stainless steel surface.

[0018] Figure 2 Comparison of weight loss and macro / micro morphology of 316L stainless steel and boronized samples after molten salt corrosion.

[0019] Figure 3 Surface morphology (a) and cross-sectional morphology (b) of untreated 316L stainless steel after corrosion in high-temperature molten salt, and EDS elemental surface scan of the cross-section.

[0020] Figure 4 The main surface morphology (a), spalling edge morphology (b), cross section before corrosion (c), and cross section after corrosion (d) of 316L boron-dipped sample after corrosion in high-temperature molten salt.

[0021] Figure 5 : EPMA results (a), XRD results (b), and schematic diagram of surface corrosion products (c) of 316L boron-dipped sample after corrosion in high-temperature molten salt.

[0022] Figure 6Surface morphology (a) and cross-sectional morphology (b) of untreated 316L stainless steel after corrosion in a high-temperature molten salt steam environment.

[0023] Figure 7 Surface morphology (a), cross-sectional morphology (b), EPMA results (c), and XRD results (d) of 316L boron-dipped samples after corrosion in a high-temperature molten salt steam environment.

[0024] Figure 8 Schematic diagram of high-temperature molten salt corrosion test apparatus. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element. When an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element present simultaneously. The terms vertical, horizontal, left, right, and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0027] See Figure 1 This application provides a method for preparing a high-temperature molten salt corrosion resistant boronized layer on a stainless steel surface, comprising the following steps S1-S2: Step S1. Perform surface pretreatment on the stainless steel substrate to remove the oxide layer on its surface; Step S2. The pre-treated stainless steel substrate is embedded in a boronizing agent, heated to the boronizing temperature under a protective atmosphere and held at that temperature, and then cooled to room temperature. Step S3. Remove the cooled stainless steel substrate from the boronizing agent and remove any residual boronizing agent from its surface.

[0028] In a specific embodiment of the present invention, the method includes the following steps: pre-treating the surface of a stainless steel substrate to remove the oxide layer on its surface; embedding the pre-treated stainless steel substrate in a boronizing agent, heating it to the boronizing temperature under a protective atmosphere and holding it at that temperature, and then cooling it to room temperature; removing the cooled stainless steel substrate from the boronizing agent and removing any residual boronizing agent from its surface. This method is the core technical solution of the present invention. Its basic concept is to form a dense boride layer on the surface of stainless steel through an embedding boronizing process, utilizing the excellent chemical and thermal stability of the boride phase to resist the corrosion of the stainless steel substrate by high-temperature chloride molten salts. Compared with the existing protective methods that require complex pre-treatment, multi-step heat treatment, or stringent process window control, the method of the present invention only requires one embedding boronizing treatment to obtain a boronized layer with excellent corrosion resistance. The process flow is greatly simplified, the operation difficulty is significantly reduced, the equipment requirements are low, and it has good process economy.

[0029] In a preferred embodiment, the stainless steel substrate is 316L stainless steel.

[0030] 316L stainless steel, due to its excellent mechanical and processing properties, is one of the most commonly used base materials for components such as pipes, valves, and storage tanks in low-temperature molten salt power generation systems. However, in high-temperature chloride molten salt environments, 316L stainless steel is highly sensitive to the dissolution and loss of Cr, resulting in significant corrosion problems. This invention addresses the corrosion resistance issue of 316L stainless steel in high-temperature chloride molten salt environments. Of course, those skilled in the art should understand that the boronizing method of this invention is also applicable to other grades of stainless steel substrates, as long as the substrate can react with the active boron atoms in the boronizing agent at the boronizing temperature to form a stable boride diffusion layer, all of which fall within the protection scope of this invention.

[0031] In a preferred embodiment, the protective atmosphere is argon, and the atmosphere surrounding the stainless steel substrate and the boronizing agent is evacuated before heating.

[0032] Specifically, a stainless steel substrate coated with boronizing agent is placed in an atmosphere tube furnace. After closing the furnace door, the atmosphere tube furnace is evacuated to remove air and moisture from the furnace cavity. After evacuation, argon gas is introduced into the atmosphere tube furnace as a protective atmosphere until the pressure inside the furnace cavity reaches atmospheric pressure (approximately 1 standard atmosphere), and argon gas is continuously circulated to maintain the inert atmosphere environment inside the furnace. Preferably, during the heating process, the flow rate of argon gas can be appropriately adjusted according to the furnace size and process requirements. By evacuating and introducing argon gas for protection, oxidation reactions between the stainless steel substrate and the boronizing agent at high temperatures can be effectively avoided, ensuring the smooth progress of the boronizing process and the quality of the boronized layer. Those skilled in the art should understand that, in addition to argon gas, other inert gases (such as nitrogen, helium, etc.) can also be used as a protective atmosphere, as long as they can effectively isolate oxygen and prevent oxidation reactions during the boronizing process; these are all equivalent alternatives to the present invention.

[0033] In a preferred embodiment, the boronizing agent is mixed and dried before use.

[0034] Specifically, after weighing the raw materials of each component according to the set mass ratio, the boronizing agent is mixed and then poured into a ball mill for ball milling to ensure uniform mixing. The mixing equipment can be a planetary ball mill or other equipment capable of achieving uniform powder mixing, such as a commercial powder mixer. The mixed boronizing agent is then dried to remove moisture. Drying can be carried out in a high-temperature drying oven or a vacuum drying oven. The drying temperature should be controlled within a range sufficient to remove moisture from the boronizing agent without causing decomposition; for example, drying can be carried out at 150°C. After drying, the boronizing agent is removed, cooled to room temperature, and ready for use. Those skilled in the art should understand that the specific formulation of the boronizing agent can be adjusted according to actual needs, as long as it can release active boron atoms under heating conditions and penetrate into the surface of the stainless steel substrate to form a boronized layer. Different boronizing agent formulations all fall within the protection scope of this invention.

[0035] This application also provides a stainless steel article having a boronized layer prepared by the aforementioned method on its surface.

[0036] The stainless steel product has a boronized layer prepared by any of the above methods on its surface. The stainless steel product forms a dense boronized layer on its surface using the method of the present invention, thereby possessing excellent resistance to high-temperature chloride molten salt corrosion. The stainless steel product can be any part or component made of stainless steel material, as long as its surface is coated with the boronized layer of the present invention. This stainless steel product can be directly applied to high-temperature molten salt environments as an industrial product with specific corrosion resistance requirements.

[0037] In a preferred embodiment, the thickness of the boronized layer is 30 μm.

[0038] Specifically, in a specific embodiment of the present invention, a stainless steel substrate is embedded in a boronizing agent, heated to the boronizing temperature under a protective atmosphere and held at that temperature, then cooled to room temperature. After removing the residual boronizing agent from the surface, the cross-section of the boronized layer is observed and measured using a scanning electron microscope to determine the thickness of the boronized layer. Under typical implementation conditions of the present invention (e.g., boronizing temperature of 850°C and holding time of 16 hours), the prepared boronized layer thickness is approximately 30 μm. This thickness of boronized layer provides sufficient corrosion protection without significantly affecting the mechanical properties of the substrate material or causing brittle cracking due to excessive thickness. Those skilled in the art should understand that the thickness of the boronized layer can be controlled by adjusting process parameters such as boronizing temperature and / or holding time. Different boronized layer thicknesses, as long as they effectively provide protection against high-temperature molten salt corrosion, fall within the protection scope of the present invention.

[0039] In a preferred embodiment, after the stainless steel product is corroded in MgCl2-KCl-NaCl molten salt at a temperature T2 of 700℃ for a time t2 of 400h, the corrosion depth D of the boronized layer satisfies D≤28.6μm. The mass percentages of each component in the MgCl2-KCl-NaCl molten salt are as follows: MgCl2 55wt%, KCl2 0.5wt%, and NaCl2 4.5wt%. The wt% represents the percentage of the mass of each component in the total mass of the molten salt. D represents the corrosion depth in μm. T2 represents the corrosion temperature in °C. t2 represents the corrosion time in h.

[0040] In actual testing, stainless steel products (i.e., samples with a boron-impregnated layer on the surface) were immersed in the above-mentioned MgCl2-KCl-NaCl molten salt and subjected to a corrosion test at 700℃ for 400 hours. After the test, the samples were removed and cooled. The corrosion depth on the cross-section was measured using a metallographic microscope or a scanning electron microscope. The test results showed that the untreated 316L stainless steel substrate sample had a corrosion depth of 134 μm under the same molten salt environment and corrosion conditions, indicating severe corrosion damage. However, the boronized layer sample of the present invention had a corrosion depth of only 28.6 μm after 400 hours of corrosion in the same molten salt environment, meaning that the corrosion depth D satisfies D≤28.6 μm. The corrosion depth of the boronized sample of the present invention is only about one-fifth of that of the untreated substrate sample, and the corrosion resistance is significantly improved. This indicates that the boronized layer of the present invention can effectively block the corrosion of the stainless steel substrate by high-temperature chloride molten salt and significantly extend the service life of stainless steel components in high-temperature molten salt environments. Those skilled in the art should understand that the parameters such as temperature, time, and molten salt composition of the corrosion test can be appropriately adjusted according to specific industrial application scenarios. Different test conditions, as long as they can verify the corrosion resistance of the boronized layer, are all within the verification scope of the present invention.

[0041] In a preferred embodiment, the MgCl2-KCl-NaCl molten salt is an unpurified molten salt.

[0042] Specifically, the unpurified molten salt refers to molten salt prepared directly using industrial-grade raw materials without additional chemical purification treatment (e.g., without purification operations such as distillation, recrystallization, or ion exchange). The molten salt may contain metal impurity ions such as Fe, Ni, and Cr, as well as impurities such as moisture and oxides. Compared to chemically purified molten salt (where impurity content is strictly controlled), unpurified molten salt is closer to the real molten salt environment in actual industrial applications, exhibiting stronger corrosiveness and requiring higher standards for protective coatings. The boronizing layer of this invention maintains excellent corrosion resistance even in unpurified molten salt, with a corrosion depth of only 28.6 μm (far smaller than the 134 μm of the substrate sample). This demonstrates the excellent engineering applicability of the boronizing layer, enabling effective protection of the stainless steel substrate under actual industrial conditions (rather than ideal laboratory purification conditions). Those skilled in the art should understand that the impurity content of unpurified molten salt may fluctuate depending on the source and batch of raw materials. However, as long as the molten salt has not undergone chemical purification and its main components (MgCl2 55wt%, KCl2 0.5wt%, NaCl2 4.5wt%) meet the limitations of this invention, it falls within the scope of protection of this invention.

[0043] In a preferred embodiment, after the stainless steel product is corroded in the steam environment of the molten salt, the boronized layer on its surface is free of corrosion pores and remains dense, and the substrate of the stainless steel product does not exhibit a depletion phenomenon in the region adjacent to the boronized layer where the mass percentage of chromium is lower than the intrinsic content of the substrate due to corrosion.

[0044] Specifically, stainless steel products (i.e., samples with a boron-diffused surface) were placed in the steam environment of the aforementioned MgCl2-KCl-NaCl molten salt (i.e., the samples did not directly contact the molten salt liquid phase, but were exposed to the steam generated above the molten salt) and subjected to corrosion tests at 700℃. After the test, the samples were removed, and the microstructure of the sample surface was observed using a scanning electron microscope. Energy dispersive spectroscopy (EDS) was used to analyze the cross-sectional chemical composition of the corroded samples. The test results showed that after molten salt steam corrosion, the untreated 316L stainless steel substrate sample developed elongated vertical pores on its surface, with a maximum corrosion depth of 154.8 μm. EDS analysis results indicated a significant chromium depletion phenomenon around the corrosion pores (i.e., the mass percentage of chromium due to corrosion was lower than the intrinsic content of the matrix), indicating that selective dissolution and loss of chromium occurred in the matrix during steam corrosion, leading to the deterioration of the matrix material properties. In contrast, after molten salt steam corrosion, the boronized layer sample of the present invention exhibited no corrosion pores and remained dense, without the vertical corrosion pores observed in the untreated substrate sample. EDS analysis results showed that the substrate of the boronized layer sample did not show a chromium content depletion phenomenon (chromium mass percentage lower than the intrinsic content of the substrate due to corrosion) in the region adjacent to the boronized layer. This indicates that the boronized layer of the present invention also has excellent protective effect in a high-temperature chloride molten salt steam environment, effectively preventing the erosion of the stainless steel substrate by molten salt steam and inhibiting the depletion and loss of chromium. Those skilled in the art should understand that the region adjacent to the boronized layer refers to the substrate region near the interface between the boronized layer and the substrate. In actual testing, the concentration distribution of chromium can be measured along the direction perpendicular to the boronized layer / substrate interface using EDS line scanning or area scanning to determine whether a chromium content depletion phenomenon (chromium mass percentage lower than the intrinsic content of the substrate) has occurred.

[0045] In a preferred embodiment, the stainless steel product is a pipe, valve, or storage tank used in a high-temperature molten salt environment.

[0046] Specifically, the aforementioned pipes, valves, or storage tanks are critical components in new energy fields such as concentrated solar power generation systems and high-temperature molten salt energy storage systems that require long-term exposure to high-temperature molten salt environments. During service, these components must simultaneously withstand both liquid-phase corrosion and vapor corrosion from high-temperature molten salt, placing extremely high demands on the corrosion resistance of the materials. The boronizing layer of this invention can provide these components with highly efficient corrosion protection, significantly extending their service life and reducing maintenance and replacement costs. Those skilled in the art should understand that, in addition to pipes, valves, or storage tanks, other stainless steel components that need to be used in high-temperature molten salt environments (such as pump bodies, heat exchangers, reactor linings, etc.) can also be protected using the boronizing layer of this invention and all fall within the scope of protection of this invention.

[0047] The technical solution of this application will be further described in detail below with reference to specific embodiments: Example 1 In this embodiment, 316L stainless steel was selected as the base material, and the rectangular sample had dimensions of 10mm × 10mm × 3mm. First, the 316L stainless steel sample was mechanically polished stepwise using silicon carbide sandpaper ranging from 180# to 1000# to remove the oxide layer and machining marks from its surface until the sample surface exhibited a uniform metallic luster. After polishing, the sample was ultrasonically cleaned in acetone for 10 minutes to remove residual oil and abrasive particles from the surface, followed by rinsing with deionized water and drying for later use.

[0048] Weigh out the raw materials of the boronizing agent according to the predetermined mass ratio, mix the raw materials and place them in a planetary ball mill for ball milling for 2 hours at a speed of 200 r / min to ensure thorough and uniform mixing. Place the mixed boronizing agent in a high-temperature drying oven and dry it at 150°C for 2 hours to remove the adsorbed moisture. After drying, remove the boronizing agent and cool it to room temperature for later use.

[0049] The pre-treated and cleaned 316L stainless steel sample was completely embedded in the dried boronizing agent, ensuring full coverage. The boron-coated sample was then placed in a quartz crucible. The crucible was placed in an atmosphere tube furnace, and the furnace door was closed. The furnace was then evacuated to a vacuum level below -0.1 MPa. After evacuation, argon gas was introduced into the furnace as a protective atmosphere until the pressure returned to atmospheric pressure (approximately 1 standard atmosphere), maintaining a continuous flow of argon at a rate of 200 ml / min. The heating program was initiated, raising the temperature to 850°C at a rate of 10°C / min and holding at 850°C for 16 hours. After holding, the heating power was turned off, allowing the atmosphere tube furnace to cool naturally to room temperature. Throughout the heating, holding, and cooling processes, argon gas was continuously introduced to maintain the protective atmosphere. After cooling to room temperature, remove the quartz crucible and take the sample out of the boronizing agent.

[0050] After removing the sample, the surface was gently polished with silicon carbide sandpaper to remove any residual boronizing agent until a bright finish was achieved. The treated sample was then rinsed with deionized water and dried to obtain a 316L stainless steel sample with a boronized layer (denoted as Sample A). The cross-section of Sample A was observed and measured using a scanning electron microscope (SEM). SEM results showed good interfacial bonding between the boronized layer and the substrate, with no obvious interfacial defects or cracks observed. The thickness of the boronized layer was approximately 30 μm, and the layer structure was dense and uniform.

[0051] Comparative Example 1 This comparative example uses 316L stainless steel samples of the same specifications as those in Example 1. After being polished with 180# to 1000# silicon carbide sandpaper, ultrasonically cleaned with acetone, rinsed with deionized water and dried, it was directly used as the control group (referred to as sample B). No boronizing treatment was performed on the surface.

[0052] Example 2 Sample A prepared in Example 1 and Sample B from Comparative Example 1 were placed in a MgCl2-KCl-NaCl mixed molten salt for liquid salt corrosion testing. The mass percentages of each component in this molten salt were: MgCl2 55wt%, KCl2 0.5wt%, and NaCl2 4.5wt%. This molten salt was unpurified, meaning it was prepared directly using industrial-grade raw materials without additional chemical purification. The corrosion test temperature was 700℃, and the corrosion time was 400h. After the test, the samples were removed, cooled, cleaned, and cross-sectional samples were prepared. The corrosion depth was measured using a metallographic microscope. A schematic diagram of the corrosion test apparatus can be found [link to schematic diagram]. Figure 8 .

[0053] Test results showed that sample B (untreated 316L stainless steel) achieved a corrosion depth of 134 μm after the corrosion test, indicating severe surface corrosion damage. This demonstrates that 316L stainless steel lacks sufficient corrosion resistance in high-temperature chloride molten salts and cannot meet practical application requirements. In contrast, sample A (boron-diffused sample) only achieved a corrosion depth of 28.6 μm after 400 hours of corrosion under the same conditions, i.e., corrosion depth D = 28.6 μm. The corrosion depth of sample A is only about one-fifth that of sample B (28.6 μm vs. 134 μm), demonstrating a significant improvement in corrosion resistance.

[0054] Further analysis of the microstructure and phase composition after corrosion was conducted using the attached figures. Figure 2 The macroscopic morphology and weight loss comparison of the etched sample are shown. For example... Figure 3 As shown, untreated 316L stainless steel (sample B) developed numerous honeycomb-like corrosion pits on its surface after molten salt corrosion. Figure 3 a) The cross-sectional morphology shows that the corrosion has obvious depth characteristics, and continuous vertical corrosion pores appear inside. Figure 3 (b) The maximum corrosion depth reached 134 μm. Combined with cross-sectional EDS elemental surface scan results, a significant decrease in Cr content was observed in the pitting region, while Mg and O elements accumulated in the pores, indicating that molten salt penetrated inward along the pores and a severe oxidation / corrosion reaction occurred. In contrast, as... Figure 4 As shown, the boron-diffused sample (sample A) maintains a smooth and dense surface after etching. Figure 4 a) Only a very small amount of slight peeling was observed in the edge area. Figure 4 b); From the cross-sectional morphology, the boronized layer after corrosion ( Figure 4 d) Compared with before corrosion ( Figure 4 c) The structure remained consistent, the interface remained tightly bonded, and no vertical corrosion pits or cracks were observed. Further EPMA and XRD analyses were performed on the boron-infiltrated samples. Figure 5 ), EPMA results ( Figure 5 a) indicates that a dense boron-rich / oxygen-rich protective layer was formed on the surface of the boron-diffused layer after corrosion; XRD pattern ( Figure 5 b) Confirmed the existence of the protective boride phase; Figure 5 c is a schematic diagram of the structure of corrosion products on the surface of the boronized layer, revealing the effective barrier mechanism of the boride layer against corrosive molten salt ions.

[0055] Comparative Example 2 This comparative example references the prior art aluminizing-thermal diffusion process disclosed in CN118792611A. Using 310S stainless steel as the substrate, the aluminized layer sample without thermal diffusion treatment after aluminizing at 800℃ for 15 hours was corroded in NaCl-KCl-MgCl2 molten salt at 800℃ for 30 hours. The surface failed to form a continuous Al2O3 protective layer, exhibiting a honeycomb-like corrosion zone approximately 78 μm thick, with a corrosion weight loss rate of 5.86 mg / cm². In contrast, the boronized layer sample of Example 1 of this invention, after corrosion in MgCl2-KCl-NaCl molten salt at 700℃ for 400 hours, showed a corrosion depth of only 28.6 μm, demonstrating significantly superior corrosion resistance compared to the prior art aluminizing-embedded process. It should be noted that due to differences in testing conditions such as corrosion temperature, corrosion time, and molten salt composition, the above comparative results only qualitatively illustrate the technical superiority of this invention.

[0056] Comparative Example 3 This comparative example uses the welding process disclosed in prior art CN113369652A, which uses Tribaloy T400 alloy powder to weld onto the surface of 316H stainless steel. After corrosion in NaCl-KCl-MgCl2 molten salt at 730℃ for 400 hours, the corrosion weight loss of the weld layer is 0.09±0.02 mg / cm², equivalent to an annual corrosion rate of 2.3 μm / a. In contrast, the boronized layer sample of Example 1 of this invention, after corrosion in MgCl2-KCl-NaCl molten salt at 700℃ for 400 hours, showed a corrosion depth of only 28.6 μm. It should be noted that the corrosion test temperature and molten salt composition of the two methods differ (730℃ vs. 700℃, and the molten salt ratio and purity are not entirely the same), therefore direct numerical comparison is not appropriate. However, both methods demonstrate that the method of this invention can obtain a beaded layer with good corrosion resistance under relatively mild process conditions.

[0057] Example 3 Sample A prepared in Example 1 and Sample B of Comparative Example 1 were placed in the vapor environment of the aforementioned MgCl2-KCl-NaCl molten salt (i.e., the samples did not directly contact the molten salt liquid phase, but were exposed to the vapor generated above the molten salt) and subjected to molten salt vapor corrosion tests at 700°C. After the test, the samples were removed, and the microstructure of the sample surface was observed using a scanning electron microscope. The cross-sectional chemical composition of the corroded samples was analyzed using energy dispersive spectroscopy (EDS).

[0058] Test results showed that after molten salt steam corrosion, sample B (untreated 316L stainless steel) developed elongated vertical pores on its surface, with a maximum corrosion depth of 154.8 μm. EDS analysis indicated significant chromium depletion around the corrosion pores, meaning the chromium content due to corrosion was lower than the intrinsic content of the matrix. This suggests selective dissolution and loss of chromium in the matrix during steam corrosion, leading to material degradation. In contrast, sample A (boronized layer sample) showed no corrosion pores and remained dense after molten salt steam corrosion, with no vertical corrosion pores observed. EDS analysis also showed that sample A's matrix did not exhibit chromium depletion due to corrosion in the region adjacent to the boronized layer. This demonstrates that the boronized layer of this invention also exhibits excellent protective effects under high-temperature chloride molten salt steam conditions, effectively preventing molten salt steam from corroding the stainless steel matrix and inhibiting chromium depletion and loss.

[0059] Figure 6 and Figure 7 The microscopic analysis results of the steam corrosion test were further presented. For example... Figure 6 As shown, untreated 316L stainless steel (sample B) exhibited severe pitting and crack morphology on its surface after steam corrosion. Figure 6 a) Cross-sectional observation reveals penetrating longitudinal corrosion pores. Figure 6 (b) Molten salt vapor erodes inward along the pores, causing penetrating damage to the substrate. However, the boron-diffused layer sample (sample A) retains a smooth and intact surface morphology after vapor corrosion. Figure 7 a) The cross-section is intact and dense, without cracks or holes. Figure 7 b). EPMA surface scan results ( Figure 7 c) shows that no obvious selective loss of elements was observed in the boronized layer, especially at the interface between the matrix and the boronized layer, where the Cr element distribution was uniform and there was no chromium depletion. XRD pattern ( Figure 7 d) This further confirms that a stable protective product layer is formed on the surface of the boronized layer after steam corrosion, demonstrating the excellent barrier performance of the boronized layer in a high-temperature molten salt steam environment.

[0060] Experimental Example The boronized layer sample prepared in Example 1 was subjected to cross-sectional metallographic analysis and SEM observation. Measurements showed that the boronized layer thickness was approximately 30 μm, with a dense and uniform internal structure free of defects such as cracks and pores. At the interface between the boronized layer and the substrate, a transition region of approximately 2-3 μm in thickness was observed, indicating a good metallurgical bond between the boronized layer and the substrate, rather than simple physical adhesion. This interfacial bonding state is beneficial for maintaining the integrity of the boronized layer under high temperature and thermal cycling conditions, avoiding peeling or cracking caused by thermal stress.

[0061] Comparison Data Summary The corrosion test results of the above embodiments and comparative examples are summarized in the following table:

[0062] The above experimental data fully demonstrate that the boronizing layer preparation method of the present invention can form a dense and uniform boronizing layer on the surface of 316L stainless steel. This boronizing layer exhibits excellent corrosion resistance in high-temperature chloride molten salt (including liquid molten salt and molten salt vapor) environments. Compared with the prior art, the method of the present invention has simple process steps, low cost of the boronizing agent, and good adaptability to the shape of the workpiece. Moreover, the boronizing layer prepared by the present invention shows excellent performance in terms of corrosion depth, porosity, and interfacial bonding quality. The boronizing layer of the present invention can be effectively applied to the surface protection of stainless steel components such as pipes, valves, or storage tanks in fields such as concentrated solar power generation systems and high-temperature molten salt energy storage systems, with significant economic benefits and broad industrial application prospects.

[0063] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0064] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a high-temperature molten salt corrosion resistant boronized layer on a stainless steel surface, characterized in that, Includes the following steps: The stainless steel substrate is pretreated to remove the oxide layer on its surface; The pre-treated stainless steel substrate is embedded in a boronizing agent, heated to the boronizing temperature under a protective atmosphere and held at that temperature, and then cooled to room temperature. The cooled stainless steel substrate is removed from the boronizing agent, and any residual boronizing agent on its surface is removed.

2. The method according to claim 1, characterized in that, The stainless steel substrate is 316L stainless steel.

3. The method according to claim 1, characterized in that, The protective atmosphere is argon, and the atmosphere surrounding the stainless steel substrate and the boronizing agent is evacuated before heating.

4. The method according to claim 1, characterized in that, The boronizing agent is mixed and dried before use.

5. A stainless steel product, characterized in that, The surface of the stainless steel article has a boronized layer prepared by the method described in any one of claims 1 to 4.

6. The stainless steel product according to claim 5, characterized in that, The thickness of the boronized layer is 30 μm.

7. The stainless steel product according to claim 5, characterized in that, When the stainless steel product is corroded in MgCl2-KCl-NaCl molten salt at a temperature T2 of 700℃ for a time t2 of 400h, the corrosion depth D of the boronized layer satisfies D≤28.6μm. The mass percentages of each component in the MgCl2-KCl-NaCl molten salt are as follows: MgCl2 55wt%, KCl2 0.5wt%, and NaCl2 4.5wt%. The wt% represents the percentage of the mass of each component in the total mass of the molten salt. D represents the corrosion depth in μm. T2 represents the corrosion temperature in °C. t2 represents the corrosion time in h.

8. The stainless steel product according to claim 7, characterized in that, The MgCl2-KCl-NaCl molten salt is an unpurified molten salt.

9. The stainless steel product according to claim 7, characterized in that, After the stainless steel product is corroded in the steam environment of the molten salt, the boronized layer on its surface is free of corrosion pores and remains dense, and the substrate of the stainless steel product does not show a depletion phenomenon in the region adjacent to the boronized layer, where the mass percentage of chromium is lower than the intrinsic content of the substrate due to corrosion.

10. The stainless steel product according to claim 5, characterized in that, The stainless steel products are pipes, valves, or storage tanks used in high-temperature molten salt environments.

Citation Information

Patent Citations

  • Surfacing method for improving wear resistance of surface of stainless steel base material

    CN113369652A

  • Stainless steel high-temperature-resistant molten chlorine salt corrosion protection method

    CN117467957A

  • Preparation method of alumina-based anticorrosive coating on surface of 310S stainless steel

    CN117587389A

  • Method for preparing chlorinated molten salt corrosion resistant layer on surface of high-temperature alloy

    CN118792611A

  • Near-equimolar-ratio multi-principal-element metal oxide anticorrosive coating as well as preparation method and application of approximately-equimolar-ratio multi-principal-element metal oxide anticorrosive coating

    CN118879103A